Image repair in the aftermath of inaccurate polling: How the news media responded to getting it wrong in 1948 and 2016. Issue 1 (3rd April 2019) - Myers, Cayce; Russell, Karen
Abstract : The US presidential elections of 1948 and 2016 produced surprise outcomes when the predicted winners ended up losing the election. Using image repair theory, this article explains the strategies the media used to repair their image in light of predicting the wrong winner. Using a qualitative analysis of news coverage that immediately followed the 1948 and 2016 presidential elections, this study finds that the media utilized similar image repair strategies of offering explanations for poor information, highlighting the media's good reporting, diminishing the harm caused by the inaccurate predictions, and justifying the inaccurate predictions of both elections. However, the media responses in 1948 and 2016 differed greatly in tone and in the utilization of a new attack strategy to deflect criticism of the media itself. These strategies suggest that media use of image restoration is limited because of the unique societal expectations placed on the press, and that the media's inaccurate 2016 predictions and subsequent attack strategies may have been contributed to the heightened criticism of mainstream news.